The Strength of Weak Ties Revisited: Further Evidence of the Role of Strong Ties in the Provision of Online Social Support. (June 2021) - Krämer, Nicole C.; Sauer, Vera; Ellison, Nicole
In this work, we challenge the assumption that weak ties play uniquely important social support roles on social network sites, particularly regarding informational support. To overcome methodological limitations of earlier research, we present a mixed-methods study. Forty-one participants were interviewed and asked to identify five weak, medium, and strong ties each and to report on perceived and actually received social support (emotional, informational, instrumental, and appraisal) associated with each. Complicating traditional understandings of "the strength of weak ties, " the qualitative analyses of actual support events show that both emotional and informational support is provided by strong ties. In an additional quantitative between-subjects study design, 352 participants were asked about various aspects of a weak, medium, or strong tie. These results indicate that participants valued their strong ties more regarding every form of support. Although there were only weak correlations between perceived and recalled actually received support, people also report actual support events with strong ties to be more helpful—overall suggesting the strength of strong ties.